Electronic word of mouth (eWOM) in the marketing context : a state of the art analysis and future directions /: a state of the art analysis and future directions. (2017) - Ismagilova, Elvira; Dwivedi, Yogesh Kumar; Slade, Emma L; Williams, Michael D
No abstract available